Một số nghiên cứu quốc tế về dạy học dự án gắn với giáo dục vì sự phát triển bền vững và một số khuyến nghị - Trần, Thị Thanh Hải; Trần, Thị Giang; Trần, Văn Nga; Lê, Văn Vinh; Đỗ, Thanh Thùy; Nguyễn, Thị Nhị (Tạp chí Giáo dục, 2025)
Project-based learning has emerged as a key educational approach to promote Education for Sustainable Development since 2010. This paper synthesizes findings from 50 international studies to explore key aspects of project-based learning implementation, including scope of expertise, implementation models, effectiveness, and challenges in implementing project-based learning with sustainability goals. The study results show that project-based learning has been widely applied in both general and higher education settings, enabling learners to gain in-depth knowledge of sustainability while building essential competencies such as critical thinking, problem solving, systems thinking, and collaboration. The paper presents some lessons for educational innovation in Vietnam in the context of using project-based learning associated with Education for Sustainable Development. Researching, analyzing and synthesizing international lessons on implementing project-based learning in Education for Sustainable Development is not only for reference but also has practical value for the process of curriculum development, teacher development, and designing innovative teaching models in general schools and universities.